Faktor- Faktor yang Berhubungan dengan Kejadian Kurang Energi Kronis (KEK) pada Ibu Hamil di Puskesmas Oesapa Kota Kupang - Teto Adinda Rihi Ga; Masrida Sinaga; Tanti Rahayu (Yayasan Literasi Sains Indonesia, 2025)
This research aims to analyze the factors related to the incidence of Chronic Energy Deficiency (KEK) in pregnant women in the work area of ​​the Oesapa Community Health Center, Kupang City in 204. This research is an observational analytical survey conducted using quantitative research with a case approach model. control which aims to determine the factors related to the incidence of Chronic Energy Deficiency (KEK) in pregnant women in the Oesapa Community Health Center working area by random sampling using quota sampling techniques. The results of the research show that the number of pregnant women with KEK 30 and those without KEK 30. Statistical test data shows that there is a significant influence between education (p-value 0.028), knowledge (0.006) and there is no significant relationship between age (p-value 0.260) , birth spacing (p-value 1.000), infectious diseases (p-value 0.112), parity (p-value 0.640), family income (p-value 0.405) with the KEK incident. In conclusion, there is a significant relationship between education and knowledge of CED in pregnant women, so that education and knowledge greatly influence the incidence of CED in pregnant women.